Computer-Aided Analysis and Design of Steel Frames - Pierson, George; Orbison, James G.; Mehringer, Vincent (Engineering Journal, 1985)
A computer package has been developed for the analysis and design of steel plane frames. The package will, with the stiffness method, analyze a plane frame and select the leastweight wide-flange section for each member within the frame. The two modules of the package, the analysis and design, may be used independently of, or in conjunction with, one another. When used together, they interact to establish an analysis/design iteration sequence by which the least weight design is obtained. Within the analysis module, graphical displays of the structure allow for visual verification of structural data as well as analytical results. The design module minimizes data entry by making design condition assumptions, all of which can be altered. By calculating internally various design parameters, such as effective column length factors, a fast, easy design session is permitted. The package is presently being used in upper-level structural analysis and steel design courses. A student using the package has the benefit of conceptualizing the entire analysis and design process rather than the fractionized procedure often presented in texts. To enhance further the students understanding of the process, the package saves all values used in the final analysis and steel section selection for verification.